Trends of English Teaching Materials in Schools: Systematic Literature Review - Munawaroh, Tatu; Ruhiyat, Yayat; Juniardi, Yudi (PPSDP International Journal of Education, 2023)
This study aims to analyze English teaching materials in schools from research articles. A systematic review was carried out in this research to show the findings of relevant studies on Teaching Materials in Schools. Three criteria were used for the systematic review: Hots, Hypertext, and teaching materials. Based on a search only eight articles were included in the systematic review of the 200 articles that were filtered based on criteria; English teaching materials in schools from 2015 to 2022. The results of this study show the tendency of using media into teaching materials, the tendency of Hots elements into the content of teaching materials, and finally the tendency of technology involvement in producing teaching material products. To follow up on this study, the tendency of Hots and hypertext-based teaching materials can be integrated to design a new framework for the development of English teaching materials in schools.